2009
DOI: 10.1103/physrevb.80.121103
|View full text |Cite
|
Sign up to set email alerts
|

Optical selection of a multiple phase order in the charge density wave condensateo-TaS3using a spectrally resolved nonequilibrium measurement

Abstract: We investigate the spectrally resolved transient reflectivity changes ⌬R͑T , , ͒ in the charge density wave ͑CDW͒ conductor o-TaS 3 . A distinct near-infrared resonance in this compound emphasizes the characteristic ⌬R͑͒ resonances, and allows a selection of coexisting CDW phases with different nonequilibrium carrier dynamics. Furthermore, the spectrally resolved ⌬R͑͒ characterizes the collective oscillations associated with the individual states. We believe that this demonstration paves the way for the optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Hence, the source of the nonlocal voltage must be present whether or not the CDW slides. in o-TaS 3 [16], and a subsequent ultrafast optical pump-probe study of o-TaS 3 also provides evidence for two types of CDW phases [17]. Discommensuration, or a lattice of topological dislocations [18] exists from the Peierls temperature to around 50 K [16].…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Hence, the source of the nonlocal voltage must be present whether or not the CDW slides. in o-TaS 3 [16], and a subsequent ultrafast optical pump-probe study of o-TaS 3 also provides evidence for two types of CDW phases [17]. Discommensuration, or a lattice of topological dislocations [18] exists from the Peierls temperature to around 50 K [16].…”
mentioning
confidence: 80%
“…Moreover, our observation of nonlocal voltages in both the pinned and sliding states reveals the existence of a carrier with long-range correlation, in addition to sliding CDWs and thermally-excited quasiparticles. Finally, we compared our observation to the coexistence of two CDWs in o-TaS 3 [16,17], and found it is closely related to topological dislocations in CDWs.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…All the temperatures indicated in this paper are corrected for heating effects by laser irradiation, which were estimated by varying the laser power. The details of our experimental and analysis of the time-resolved spectroscopy are described in previous papers [13][14][15]. By the optical measurement described herein, one obtains the difference in reflectivity (R) from that of equilibrium state as a function of time; ∆R(t).…”
Section: Methodsmentioning
confidence: 99%
“…Usually anomalous T -dependence of τ exp is observed in many gapped systems, for example, phase-ordered systems showing an energy gap opening in the electron band below the transition temperature T c . It has been found that a wide variety of superconductors [1][2][3][4][5][6][7][8][9][10][11][12] and density-wave compounds [13][14][15][16][17][18][19] show diverging behavior of τ exp near T c , as confirmed by femtosecond time-resolved optical spectroscopy [1,4,5,[7][8][9][10][11][12][13][14][15][16][17]19]. The divergence of τ exp in these gapped systems is believed to result from recursive energy transfer between electrons and phonons.…”
mentioning
confidence: 96%